Interleukin 17 B regulates colonic myeloid cell infiltration in a mouse model of DSS-induced colitis - Zhang, Xiaomin; Zhang, Xiaokai; Song, Xiaomei; Xiang, Chuanying; He, Chunmei; Xie, Yu; Zhou, Yangyang; Wang, Ning; Guo, Gang; Zhang, Weijun; Li, Yan; Liu, Kaiyun; et al. (Frontiers in Immunology, 2023)
Cytokines play vital roles in the pathogenesis of inflammatory bowel disease. IL17B is protective in the development of colitis. However, how IL17B regulates intestinal inflammation and what cells are regulated by IL17B is still unknown. Here, we aimed to illustrate the IL17B dependent cellular and molecular changes in colon tissue in a mouse colitis model. The results showed that IL17B expression in colon tissues was elevated in inflamed tissues than non-inflamed tissues of IBD patients. Wild type (WT) and Il17b deficient (Il17b-/-) mice were given 2.5% dextran sodium sulfate (DSS) water, and in some case, Il17b-/- mice were treated with recombinant mouse IL17B. IL17B deficiency resulted in severe DSS-induced colitis with exaggerated weight loss, shorter colon length, and elevated proinflammatory cytokines in colon. Reconstitution of Il17b-/- mice with recombinant IL17B alleviated the severity of DSS-induced colitis. Single cell transcriptional analyses of CD45+ immune cells in colonic lamina propria revealed that loss of IL17B resulted in an increased neutrophil infiltration and enhanced inflammatory cytokines in intestinal macrophages in colitis, which were confirmed by real-time PCR and flow cytometry. IL17B treatment also inhibited lipopolysaccharide-induced inflammation in bone marrow-derived macrophages and mice. IL17B inhibits colitis by regulating colonic myeloid cell response. It might represent a novel potential therapeutic approach to treat the colitis.